Hybrid Strategy of Two-Level Cervical Artificial Disc and Intervertebral Cage: Biomechanical Effects on Tissues and Implants. Issue 47 (November 2015) - Chung, Tzu-Tsao; Hueng, Dueng-Yuan; Lin, Shang-Chih
Abstract : Abstract: This numerical study aimed to evaluate tissue and implant responses to the hybrid surgery (HS) of cervical artificial disc replacement (C-ADR) and anterior cervical discectomy and fusion (ACDF). Four hybrid strategies of two-level C-ADR and ACDF were compared in terms of adjacent segment degeneration (ASD) and implant failure. The rotary C-ADR and semirigid ACDF have been extensively used in the multilevel treatment of cervical instability and degeneration, but the constrained mobility at the ACDF segments can induce postoperative ASD problems. Hybrid surgery of C-ADR and ACDF has been an alternative to provide the optimal tradeoff between surgical cost and ASD problems. The biomechanical effects of hybrid strategies warrant thorough investigation for the two-level instrumentation. Based on computed tomography imaging, a nonlinear C2–C7 model was developed and validated by cadaveric and numerical data. Four strategies of inserting the C-ADR and ACDF into the C4–C6 segments were systematically arranged as PP (2 peek cages), AA (2 artificial discs), PA, and AP. The biomechanical behavior of these 4 strategies was evaluated in terms of motion and stresses of discs, facet forces, stresses of C-ADR and ACDF, and C-ADR motion. The constrained mobility of the ACDF segment worsened the kinematic and mechanical demands of the adjacent segments and artificial discs. The C-ADR articulation provided higher mobility than the replaced disc of the intact construct, making it an effective buffer to accommodate the compensated mobility and load from the ACDF segment. Consequently, the ASD progression of the AA construct was most restricted, followed by the PA, AP, and PP construct. The PA strategy is a tradeoff to preserve mobility and reduce cost. The C-ADR of the PA construct preserves the mobility of the C5/C6 segment and shares the transferred motion and loads of the fused C4/C5 segment. The PA construct shows optimal biomechanical results for minimizing ASD and implant failure, whereas the AP strategy is only recommended when cranial degeneration is the major concern.